The Case for Health Reparations - Derek Ross Soled; Derek Ross Soled; Avik Chatterjee; Avik Chatterjee; Daniele Olveczky; Edwin G. Lindo (Frontiers Media S.A., 2021)
The disproportionate impact of COVID-19 on racially marginalized communities has again raised the issue of what justice in healthcare looks like. Indeed, it is impossible to analyze the meaning of the word justice in the medical context without first discussing the central role of racism in the American scientific and healthcare systems. In summary, we argue that physicians and scientists were the architects and imagination of the racial taxonomy and oppressive machinations upon which this country was founded. This oppressive racial taxonomy reinforced and outlined the myth of biological superiority, which laid the foundation for the political, economic, and systemic power of Whiteness. Therefore, in order to achieve universal racial justice, the nation must first address science and medicine's historical role in scaffolding the structure of racism we bear witness of today. To achieve this objective, one of the first steps, we believe, is for there to be health reparations. More specifically, health reparations should be a central part of establishing racial justice in the United States and not relegated to a secondary status. While other scholars have focused on ways to alleviate healthcare inequities, few have addressed the need for health reparations and the forms they might take. This piece offers the ethical grounds for health reparations and various justice-focused solutions.